Kindred's international law, chiefly as interpreted and applied in Canada - Saunders, Phillip; Currie, Robert J.; Akhavan, Payam; Brunnée, Jutta; Van Ert, Gib; McDorman, Ted L.; Mégret, Frédéric; Mgbeoji, Ikechi; Mickelson, Karin; Reif, Linda C.; Waters, Christopher P. M.; Castel, J.-G. (Emond, 2019)
"The book delivers a comprehensive overview of the foundational concepts, principles, sources, and institutions of the international legal system and how they are experienced and practiced domestically and in foreign relations"– Résumé de l'éditeur.